Structural basis for Marburg virus VP35–mediated immune evasion mechanisms - Ramanan, Parameshwaran (National Academy of Sciences, 2012)
Filoviruses, marburgvirus (MARV) and ebolavirus (EBOV), are causative agents of highly lethal hemorrhagic fever in humans. MARV and EBOV share a common genome organization but show important differences in replication complex formation, cell entry, host tropism, transcriptional regulation, and immune evasion. Multifunctional filoviral viral protein (VP) 35 proteins inhibit innate immune responses. Recent studies suggest double-stranded (ds)RNA sequestration is a potential mechanism that allows EBOV VP35 to antagonize retinoic-acid inducible gene-I (RIG-I) like receptors (RLRs) that are activated by viral pathogen–associated molecular patterns (PAMPs), such as double-strandedness and dsRNA blunt ends. Here, we show that MARV VP35 can inhibit IFN production at multiple steps in the signaling pathways downstream of RLRs. The crystal structure of MARV VP35 IID in complex with 18-bp dsRNA reveals that despite the similar protein fold as EBOV VP35 IID, MARV VP35 IID interacts with the dsRNA backbone and not with blunt ends. Functional studies show that MARV VP35 can inhibit dsRNA-dependent RLR activation and interferon (IFN) regulatory factor 3 (IRF3) phosphorylation by IFN kinases TRAF family member-associated NFkb activator (TANK) binding kinase-1 (TBK-1) and IFN kB kinase e (IKKe) in cell-based studies. We also show that MARV VP35 can only inhibit RIG-I and melanoma differentiation associated gene 5 (MDA5) activation by double strandedness of RNA PAMPs (coating backbone) but is unable to inhibit activation of RLRs by dsRNA blunt ends (end capping). In contrast, EBOV VP35 can inhibit activation by both PAMPs. Insights on differential PAMP recognition and inhibition of IFN induction by a similar filoviral VP35 fold, as shown here, reveal the structural and functional plasticity of a highly conserved virulence factor.